A study on the effectiveness of school net learning system at urban and rural schools in Negeri Sembilan / Noor Salinda Salim - Salim, Noor Salinda (Faculty of Business Management, 2005)
The purpose of this research is to examine the level of interest among students and teachers in urban and rural schools and the relationship between the effects using the School Net in E-Iearning. Finally, the study is looks into the system whether it has really given an impact in improving the learning system in school. This study employed prepared survey instrument whereby 25% respondents were selected from a sampling frame of 298 schools throughout Negeri Sembilan (first phase). The data obtained were them analyzed. Descriptive tables and simple cross tabulations are used to test the data. The findings show that most of the users are interested with School Net in their learning system. They are aware of the system being introduced and have developed an extra dimension about new learning in terms of the infrastructure in their schools but dissatisfaction did occur among the students and teachers due to the use of English language and ill equipped infrastructure. Hence, it is suggested that by using that School Net in Elearning at school learning system analysis the students will be more effective and perhaps better academic results performance can be achieved by them in the future.